Testing for the Diffusion Matrix in a Continuous-Time Markov Process Model with Applications to the Term Structure of Interest Rates - Fuchun Li (Bank of Canada, 2015)
The author proposes a test for the parametric specification of each component in the diffusion matrix of a d-dimensional diffusion process. Overall, d (d-1)/2 test statistics are constructed for the off-diagonal components, while d test statistics are constructed for the main diagonal components. Using theories of degenerate U-statistics, each of these test statistics is shown to follow an asymptotic standard normal distribution under null hypothesis, while diverging to infinity if the component is misspecified over a significant range. Our tests strongly reject the specification of diffusion functions in a variety of popular univariate interest rate models for daily 7-day eurodollar spot rates, and the specification of the diffusion matrix in some popular multivariate affine term-structure models for monthly U.S. Treasury yields.
Keywords: C12; C14; E17; E43; G12; G20; 330; Asset pricing; Interest rates; Econometric and statistical methods